PENGARUH KINERJA DAN KOMPETENSI KOMUNIKASI PETUGAS PLKB TERHADAP KEBERHASILAN PROGRAM KB DI KECAMATAN WOJA-DOMPU - Abdul Basyar; Mahmud Mahmud; Shoalihin Shoalihin (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
This explanatory quantitative study examines the impact of performance and communication competence of Family Planning Field Workers (PLKB) on the success of the family planning program in Woja, Dompu. Data from 65 couples of childbearing age, collected via purposive sampling and Likert-scale questionnaires, were analyzed using SEM-PLS. The structural model demonstrated strong predictive power (R² = 70.5%). Hypothesis testing revealed a crucial finding: workers' administrative performance had a significant but negative effect (P=0.015; β=-0.218), indicating that a rigid, target-oriented approach triggers resistance in rural communities. Conversely, communication competence emerged as the dominant predictor with a highly significant positive effect (P=0.000; β=0.962). Simultaneously, both variables showed a significant impact. The study concludes that successful implementation in communal cultures necessitates a dialogic and empathetic approach. The government is advised to evaluate PLKB assessment standards by prioritizing cross-cultural communication soft skills.